A too-long anterior process of the calcaneus: a report of 31 operated cases - El Hayek, Toni (2009)
A too-long anterior process of the calcaneus is one of the causes of repeated sprained ankles or painful feet in the child or adolescent that is often ignored and misdiagnosed. Among 31 cases of adolescents having consulted for these symptoms, a too-long anterior process of the calcaneus was discovered on radiographs, and explored in detail with a computed tomography scan or an MRI. The decision for surgical resection was taken considering the discomfort expressed by these children. The intraoperative observation corroborated the radiological findings and permitted a better understanding of the mechanisms responsible for the pain, the repeated sprained ankles and other instabilities. The surgical resection, which is a simple procedure, gave very good results. One must nevertheless be aware of the possible secondary lesions because of repeated sprained ankles: breakage of the lateral ligaments of the ankle and external malleolus nonunion or talus osteochondritis, which can compromise the operation's result, if they are not treated simultaneously.